THE EFFECT OF IMPLEMENTATION DIFFERENTIATED INSTRUCTION FOR ENHANCING MATHEMATICAL COMPETENCE IN THE LAST DECADE - Peni Anggareni; Dadang Juandi (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The objective of this research is to describe the effect of implementation Differentiated Instruction (DI) for enhancing mathematical competence in the last decade of primary, secondary, and high/vocational school students. The study method is a Systematic Literature Review (SLR). The dataset comprised 15 articles focusing on the effect of DI on enhancing mathematical competence. The samples were extracted from published indexed which published between 2013 and 2022. The focus of this study is to describe the impact of Implementation DI for enhancing mathematical competence in the last decade, in terms of research period, academic level, sample size, mathematics content, the authors' geographical distribution., and research methodologies. By employing SLR, over the decade, the number of studies increased., except 2019-2020, the most of the studies were conducted on secondary school students, most of the subjects with 30 or more, the most content mathematics were geometry, the most empirical investigations were Indonesia and Philippines, and the most research methodologies conducted by quasi experiment. In accordance with a full-text analysis of 15 published papers, DI potentially could improve mathematical competence, especially achievement and performance, but only a few articles that discuss problem solving, understanding, creative thinking, critical thinking, and mathematics connection.